Correlation of Gadget Use on Social Behavior and Learning Interest of Elementary School Students - Safitri Dwi Aryanti Muchsin Nur; Diki Rukmana (Lectura : Jurnal Pendidikan, 2023)
With the changes in the advancement of knowledge of technology there is the influence of globalization especially in the field of interaction tools namely gadgets. This can have an impact especially on elementary school children who use gadgets for a long time every day resulting in a decrease in the quality of interest in learning and social behavior. The purpose of this research is to determine the relationship between the use of gadgets and the social behavior and learning interest of elementary school students by looking for the factors causing the influence of these three variables especially students in class 1-6 in the city of Bekasi. The research instrument consisting of 35 questionnaire items was distributed using a survey research design at Sekolah Dasar (SD) Negeri Harapan Baru 1 Bekasi with a sample size of 100 students. Data processing used the SmartPls application to evaluate the outer model, inner model, analyze instrument validation and hypothesis testing. The findings of the analysis of the outer loading factor results obtained out of 35 items there were 7 question items that did not meet the requirements because they had an outer loading factor <0.700 so that only 28 statement items were used in the research. The results of the research hypothesis were that the original sample value was positive, the tendency for the correlation variable was one-way as seen from the p-value 0.000. In conclusion, there is a significant relationship of using gadgets on behavior and social interests.